CARA BERPIKIR SISWA SEKOLAH DASAR DALAM MENYELESAIKAN SOAL OPERASI PERKALIAN - Nurul Ilmiyah (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2018)
Multiplication is one of the important materials taught in elementary school because it is very often found its application in everyday life. In addition, mathematical topics for higher levels still use multiplication operations. In essence the plot is a recurrent sum, but not necessarily the multiplication concept is taught in a way that depends only on repeated summations. Students need to be trained to shift from thinking adding (additive thinking) to multiplicative thinking. Multiplicative Thinking is a prerequisite for being able to solve problems involving fractions, decimal numbers, percent numbers, and comparisons. The purpose of writing this article is to identify and describe the way of thinking elementary school students, especially students in grade 3 and 4 in solving multiplication counting problems. The classification of students into the form of multiplicative or additive ways of thinking seen from the work of students then grouped based on its characteristics. Perkalian merupakan salah satu materi penting yang diajarkan pada jenjang sekolah dasar karena amat sering dijumpai penerapannya dalam kehidupan sehari-hari. Selain itu, topik-topik matematika untuk jenjang ynag lebih tinggi masih menggunakan operasi perkalian. Pada dasarnya perklaian merupakan penjumlahan yang berulang, namun tidak seharusnya konsep perkalian diajarkan dengan cara hanya bergantung pada penjumlahan berulang semata. Siswa perlu dilatih untuk bergeser dari berpikir penjumlahan (additive thinking) ke berpikir perkalian (multiplicative thinking). Multiplicative Thinking adalah prasyarat untuk untuk dapat menyelesaikan permasalahann yang melibatkan pecahan, bilangan desimal, bilangan persen, dan perbandingan. Tujuan penulisan artikel ini adalah mengidentifikasi dan mendeskripsikan cara berpikir siswa sekolah dasar terutama siswa kelas 3 dan 4 dalam menyelesaikan soal operasi hitung perkalian. Adapun pengklasifikasian siswa ke dalam bentuk cara berpikir multiplicative atau additive dilihat dari hasil pekerjaan siswa kemudian dikelompokkan berdasarkan ciri-cirinya.